Economic Conditions, Parental Employment and Health of Newborns - Gerard J. van den Berg; Alexander Paul; Steffen Reinhold (Institute of Labor Economics (IZA), 2018)
We examine whether economic downturns are beneficial to health outcomes of newborn infants in developed countries. For this we use merged population-wide registers on health and economic and demographic variables, including the national medical birth register and intergenerational link registers from Sweden covering 1992–2004. We take a rigorous econometric approach that exploits regional variation in unemployment and compares babies born to the same parents so as to deal with possible selective fertility based on labor market conditions. We find that downturns are beneficial; for example, a one-percentage-point increase in the unemployment rate during pregnancy reduces the probability of having a birth weight less than 1,500 grams or of dying within 28 days of birth by 10–15%. Effects are larger in low socio-economic status households. Health improvements cannot be attributed to the parents' own employment status. The results suggest pathways through stress and air pollution.
Keywords: I1; J1; 330; recession; unemployment; fertility; infant health; stress